THE EFFECTIVENESS OF INTRAVITREAL ANTI-VEGF INJECTION IN EALES' DISEASE: A CASE REPORT: Poster Presentation - Case Report - General practitioner - Khairani Azizah Ardityastiti; Halida Wibawaty (Majalah Oftalmologi Indonesia, 2023)
Introduction : Eales’ Disease (ED) is an idiopathic inflammatory retinal vasculitis, affecting retinal veins of small and large caliber that results in extraretinal neovascularization with vitreous hemorrhage. The etiopathogenesis of ED is poorly understood. However, many studies have attributed inflammation as a response to mycobacterium tuberculosis. Treatment of this disease can be done with corticosteroids, anti-VEGF therapy, laser photocoagulation, and vitreoretinal surgery. Case Illustration : We reported a patient, a 31-year-old woman with complaints of blurred vision and floaters in both eyes. An initial examination showed the visual acuity of the RE was 0,1F1 and the LE was 0,1. Examination of the posterior segment found perivascular exudate and peripheral retinal neovascularization. We performed an OCT examination on both eyes and found that there was extensive macular edema, especially in the RE. Patient was diagnosed with ED and received steroidsas an initial treatment. But there was no improvement in both eyes. In addition, patient received two anti-VEGF injections in the RE and one injection in the LE and showed good improvement. After that injection, the posterior segment showed very minimal lesions on the macula and repeated OCT results showed normal central macular thickness. Discussion : Anti-VEGF may also play a role in the treatment and management of ED. This is because, besides inflammation, there is an increased expression of VEGF in vitreous patients with ED. Several case reported there is significant improvement in anti-VEGF injection in the management of patients with ED. Conclusion : Intravitreal anti-VEGF injection shows good results in ED that did not improve with steroid treatment.